CORRELATION OF AGGREGATED BETA AMYLOID LEVEL IN PLASMA WITH MoCA AND MMSE AMONG PATIENTS WITH TYPE 2 DIABETES WITH DEMENTIA - Ardales, Michelle; Sy, Rosa Allyn; Olaivar, Marietta; Cipriano, Critopher Cipriano; Bacalso, Mary Nel; Esguerra, Miguel (Journal of the ASEAN Federation of Endocrine Societies, 2022)
INTRODUCTION Type 2 DM as a risk factor for Alzheimer’s disease (AD) has been studied in recent years; however, no clear evidence of association has been found. As potential biomarker for AD, plasma beta amyloid is likewise under study by researchers. We examined the correlation between plasma beta amyloid levels and cognitive function among type 2 DM patients with dementia as indicated by their neurocognitive assessment scores. This study hopes to devise a less invasive early detection of AD among patients with diabetes. METHODOLOGY In this cross-sectional study, 100 patients with type 2 DM and dementia underwent plain cranial CT scan, plasma beta amyloid, MMSE and MoCA. Patients were categorized as having vascular dementia using the NINDS-AIREN Criteria. Elevated plasma beta amyloid was used as biomarker for AD. RESULTS Among type 2 DM patients with dementia, there is an increased prevalence of AD (46.7%) as shown by the elevated beta amyloid level. The prevalence of vascular dementia is 6%. Among patients with non-vascular dementia, 51.3% have elevated beta amyloid. There is no significant correlation between both MMSE score and beta amyloid (r=-0.0192, p=0.8557), and between MoCA score and beta amyloid (r=0.0939, p=0.3731). The results do not show significant correlation between MMSE and MoCA scores with beta amyloid level among patients with AD. CONCLUSION Using the beta amyloid as biomarker, the study suggests a link between AD and type 2 DM, however, we recommend further researches to ascertain the use of plasma beta amyloid as a less invasive screening for AD among patients with diabetes.